Transitioning to quantum-safe cryptography on IBM Z - White, Bill (Telecommunications engineer); Andre, Didier; Arquero, Gregg; Bajaj, Ritu; Cronin, Joe; Dames, Anne; Lyksborg, Henrik; Miranda, Alexandra; Weiss, Maxwell (IBM Redbooks, 2022)
As cyberattacks continue to increase, the cost and reputation impacts of data breaches remain a top concern across all enterprises. Even if sensitive data is encrypted and is of no use now, cybercriminals are harvesting that data because they might gain access to a quantum computer that can break classical cryptographic algorithms sometime in the future. Therefore, organizations must start protecting their sensitive data today by using quantum-safe cryptography. This IBM® Redbooks® publication reviews some potential threats to classical cryptography by way of quantum computers and how to make best use of today's quantum-safe capabilities on the IBM Z platform. This book also provides guidance about how to get started on a quantum-safe journey and step-by-step examples for deploying IBM Z® quantum-safe capabilities. This publication is intended for IT managers, IT architects, system programmers, security administrators, and anyone who needs to plan for, deploy, and manage quantum-safe cryptography on the IBM Z platform. The reader is expected to have a basic understanding of IBM Z security concepts.